Estudo fitoquímico com fins farmacológicos da alga bentônica Caulerpa racemosa - Lorenzo, Vitor Prates (2010)
Caulerpa racemosa (Forssk.) J.Agardh is a green seaweed widely distributed in Brazil northeast, living on rocks or in association with other seaweeds. Pharmacoligacal studies related the antimicrobial and repellent activities of the extract. The literature related the presence of alkaloids, terpenoids, steroids and some others class of metabolites. The purpose of this work is expand the phytochemical and pharmacoligacal, performing tests that related significant antiinflammatory and antinociceptive action. The fresh sample was exhaustively extracted with hexane, chloroform, ethyl acetate and methanol in a crescent gradient of polarity. The chloroform extract was cromatographed by usual techniques leading to the isolament of four compounds, being three related at the first time in the family Caulerpaceae. The isolated constituent from methanolic extract were identified by spectroscopy analysis such as Infra Red, 1H and 13C NMR spectroscopy, two dimension techniques (COSY, NOESY, HSQC, HMBC) and comparison with literature data.